2009
DOI: 10.1002/art.24430
|View full text |Cite
|
Sign up to set email alerts
|

Association of concomitant fibromyalgia with worse disease activity score in 28 joints, health assessment questionnaire, and short form 36 scores in patients with rheumatoid arthritis

Abstract: Objective. To study the association of the presence of fibromyalgia (FM) with the Disease Activity Score in 28 joints (DAS28), the Health Assessment Questionnaire (HAQ), and the Medical Outcomes Study Short Form 36 (SF-36) health survey in patients with rheumatoid arthritis (RA). Methods. A total of 270 outpatients with RA were enrolled in a prospective cross-sectional study. The patients underwent clinical evaluation and application of the HAQ and SF-36 questionnaires. Disease activity was evaluated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
115
4
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 16 publications
19
115
4
11
Order By: Relevance
“…The strong association between remaining pain and functional impairment at baseline was not a surprising finding, as disability and pain are very strongly correlated 16. Previous data have implicated disability as a strong marker for chronic pain 17, and research earlier showed that RA patients with concomitant fibromyalgia display increased disability compared to patients without fibromyalgia 18, 19. From our data, we could not detect prevalence of fibromyalgia, which was not in the scope of the study, but earlier investigations have shown that the prevalence of chronic widespread pain may be increased by 10‐fold in RA 18.…”
Section: Discussionmentioning
confidence: 90%
“…The strong association between remaining pain and functional impairment at baseline was not a surprising finding, as disability and pain are very strongly correlated 16. Previous data have implicated disability as a strong marker for chronic pain 17, and research earlier showed that RA patients with concomitant fibromyalgia display increased disability compared to patients without fibromyalgia 18, 19. From our data, we could not detect prevalence of fibromyalgia, which was not in the scope of the study, but earlier investigations have shown that the prevalence of chronic widespread pain may be increased by 10‐fold in RA 18.…”
Section: Discussionmentioning
confidence: 90%
“…Some studies reported that depression is associated with reduced health status, as well as higher pain, fatigue, and reduced QOL (9,21,25). According to the present study, depression which appears to be a key factor affecting QOL should be prevented.…”
Section: Atapoor Et Al (15) 2002mentioning
confidence: 56%
“…), депрессия, фи-бромиалгия, особенности психики, вторичные дегенера-тивные изменения в суставах и др. [94][95][96][97], что приводит к некорректной оценке активности заболевания [94]. Примечательно, что у пациентов с РА, имеющих вторич-ную фибромиалгию, по данным УЗИ признаки воспале-ния суставов выражены в меньшей степени, чем у боль-ных без фибромиалгии при сходных значениях индекса DAS [98].…”
unclassified